Otra oportunidad para Fortunata - Ventura, Laura (Verba hispanica, 2020)
Almudena Grandes takes the Galdos' National Episodes as a model to create her own multi-novel saga, Episodes of an endless war. In Frankenstein 's Mother(2020), the last novel in this series which explores the Spanish postwar period, two particular techniques make Grandes, both a writer and a historian, Benito Pérez Galdós 's literary heiress. The first, a formal one, is her episodic and choruslike construction of the narration, where she gives a voice to anonymous characters in history and society; the second is her rereading of Fortunata and Jacinta, where she creates her heroine, María, as though as a mirror image of Galdos' Fortunata.
Keywords: Grandes, Almudena; Pérez Galdós, Benito; realistic novel; realistični roman; Spanish literature; španska književnost